The Iconography of Kitchen Wallpaper in Canada - Owens, Gwendolyn (Cuizine)

(untitled) (McGill University Library, 2009)
AbstractKitchen wallpaper is a relatively modern development. The types of images that we associate with kitchen wallpaper—what we now think of as “normal” or “usual” designs—tell us a lot about when it was developed in the early part of the 20th century, particularly the 1920s. Its iconography provides a key to understanding how kitchen design has evolved and how the user of the kitchen has been regarded over time. This article pays particular attention to the development and distribution of kitchen wallpaper in Canada.